Pembentukan Kesadaran Kepatuhan Kepabeanan melalui Edukasi Kebijakan Impor, Regulasi Thrifting dan Dampaknya terhadap Industri Lokal - Anisa Kusumawardani; Andi Kartika; Maulana Ihsan Yusufi Suyatno; Adhitya Yoga Prasetya; Zati Rizka Fadhila; Dhian Andanarini Minar Savitri (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service activity aimed to enhance students’ awareness of customs compliance through education on import policies, thrift clothing regulations, and their impacts on local industries. The program was conducted at Kantor Bea Cukai Tanjung Emas on October 22, 2025, involving 34 Diploma III students specializing in Export-Import studies who were preparing for internships in MSMEs engaged in international trade activities. The activity employed an educative-participatory approach using the Community Based Research (CBR) method through educational sessions, interactive discussions, case studies, and reflection activities. The results showed that participants experienced increased understanding regarding import regulations, the prohibition of imported secondhand clothing, customs supervision, and the economic impacts of illegal imports on domestic industries. In addition, the activity succeeded in fostering critical awareness among students regarding the importance of legal compliance and support for local products in the era of globalization and digital trade.